Phylogeny of Vibrio cholerae Based on recA Sequence - Stine, O. Colin (American Society for Microbiology, 2000)
We sequenced a 705-bp fragment of the recA gene from 113 Vibrio cholerae strains and closely related species. One hundred eighty-seven nucleotides were phylogenetically informative, 55 were phylogenetically uninformative, and 463 were invariant. Not unexpectedly, Vibrio parahaemolyticus and Vibrio vulnificus strains formed out-groups; we also identified isolates which resembled V. cholerae biochemically but which did not cluster with V. cholerae. In many instances, V. cholerae serogroup designations did not correlate with phylogeny, as reflected by recA sequence divergence. This observation is consistent with the idea that there is horizontal transfer of O-antigen biosynthesis genes among V. cholerae strains.